Magnetic anisotropy in square pyramidal cobalt(ii) complexes supported by a tetraazo macrocyclic ligand. Issue 42 (9th October 2020) - Cui, Hui-Hui; Ding, Man-Man; Zhang, Xiu-Du; Lv, Wei; Zhang, Yi-Quan; Chen, Xue-Tai; Wang, Zhenxing; Ouyang, Zhong-Wen; Xue, Zi-Ling
Abstract : Positive magnetic anisotropies of two square-pyramidal cobalt(ii ) complexes have been revealed by magnetic measurements, HF-EPR spectroscopy and theoretical calculations. Abstract : Two five-coordinate mononuclear Co(ii ) complexes [Co(12-TMC)X][B(C6 H5 )4 ] (L = 1, 4, 7, 10-tetramethyl-1, 4, 7, 10-tetraazacyclododecane (12-TMC), X = Cl − (1 ), Br − (2 )) have been studied by X-ray single crystallography, magnetic measurements, high-frequency and -field EPR (HF-EPR) spectroscopy and theoretical calculations. Both complexes have a distorted square pyramidal geometry with the Co(ii ) ion lying above the basal plane constrained by the rigid tetradentate macrocyclic ligand. In contrast to the reported five-coordinate Co(ii ) complex [Co(12-TMC)(NCO)][B(C6 H5 )4 ] (3 ) exhibiting easy-axis anisotropy, an easy-plane magnetic anisotropy was found for 1 and 2 via the analyses of the direct-current magnetic data and HF-EPR spectroscopy. Frequency- and temperature-dependent alternating-current magnetic susceptibility measurements demonstrated that complexes 1 and 2 show slow magnetic relaxation at an applied dc field. Ab initio calculations were performed to reveal the impact of the terminal ligands on the nature of the magnetic anisotropies of this series of five-coordinate Co(ii ) complexes.